PENGARUH METODE LATIHAN POWER OTOT LENGAN TERHADAP KEMAMPUAN SMASH BULU TANGKIS PADA PB. MANDIRI PUTRA KOTA PEKANBARU - Peni Elisman; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abtract : Based on the observations of researchers in the field the ability Smash Badminton At PB. Putra Mandiri Pekanbaru City still low. This is evident from the weakness of the arm muscle power athletes, because when doing so required badminton smash fast and precise movements. Therefore Power bicep be one important factor in giving effect to the smash ability. The purpose of this study was to determine the effects of exercise forearm muscle power to smash the ability of badminton in the PB. Putra Mandiri Pekanbaru. The population in this study is the player PB. Kota Putra Mandiri Pekanbaru.yang amounted to 15 people. The sample in this study using the technique of total sampling, that the sample in this study amounted to 15 people. Research instrument used was a test forehand smash. The data obtained will be in the analysis by using t-test. Based on the results of 7937 taccount> 1,791 (ttabel) and then the hypothesis is accepted that influences of the exercise arm muscle power to smash ability badminton on the PB. Putra Mandiri Pekanbaru.Keywords : Mucular arms, Smash Skill